2019
DOI: 10.1128/aem.01700-19
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Shewanella oneidensis Thioredoxin in Regulation of Cellular Responses to Hydrogen and Organic Peroxides

Abstract: The thioredoxin (Trx) and glutaredoxin (Grx) antioxidant systems are deeply involved in bacterial response to oxidative stress, but to date, we know surprisingly little about the roles of these systems in response to reactive oxygen species (ROS) other than hydrogen peroxide (H2O2). In this study, we used Shewanella oneidensis, an environmental bacterium, as a research model to investigate the roles of Trx and Grx in oxidative stress response because it has functionally intertwined ROS responsive regulators Ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…This was largely achieved in the dsbD-negative background. In S. oneidensis, DsbD is the only thiol:disulfide interchange protein that passes electrons from cytoplasmic Trx1 to CCM for the reduction of oxidized apocyts c (56). In the absence of DsbD, maturation can occur only on apocyts c with free thiol groups resulting from the depletion of DsbA proteins, eliminating the interference from those that are oxidized independently of DsbA proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This was largely achieved in the dsbD-negative background. In S. oneidensis, DsbD is the only thiol:disulfide interchange protein that passes electrons from cytoplasmic Trx1 to CCM for the reduction of oxidized apocyts c (56). In the absence of DsbD, maturation can occur only on apocyts c with free thiol groups resulting from the depletion of DsbA proteins, eliminating the interference from those that are oxidized independently of DsbA proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular sulfur homeostasis should be carefully maintained because H 2 S and cysteine in vast excess promote oxidative damages by inhibiting catalases (Park and Imlay, 2003;Wu et al, 2015). Consistently, all components of thiol-based antioxidant systems of YPIII are most highly induced upon exposure to H 2 O 2 , conceivably requiring an active metabolism and fast shuttling of sulfur species (Feng et al, 2019). In parallel, genes for iron/manganese transport system are highly induced by exogenous H 2 O 2 .…”
Section: Discussionmentioning
confidence: 98%
“…Other putative OxyR regulon members that were induced but not among the top 10 included katG, trxB, ahpC, and sufABC (Fe-S cluster assembly proteins; Table 2). Intriguingly, the entire thioredoxin and glutathione antioxidant systems, which play a supporting role in combating oxidative stress in many bacteria (Feng et al, 2019), were found to be highly induced by H 2 O 2 (for instance, YPK_RS20590 was induced 689-fold), implying that these systems may have more significant contribution in protecting YPIII cells from oxidative damage. It is also worth mentioning that the oxyR gene was transcribed at substantially elevated levels (4.5-fold) upon H 2 O 2 stress (Table 2), suggesting that the regulator per se is also subjected to quantity control, in addition to activity transformation upon oxidation.…”
Section: Transcriptomics Analysis Of Ypiii In Response To H 2 O 2 Stressmentioning
confidence: 99%
“…strain CF-1 confer more protection to E. coli when exposed to oxidative conditions with ferric iron than does the endogenous gene trxA. As mentioned above, the TrxA protein from E. coli is a thioredoxin directly related to oxidative protection [7,57].…”
Section: The Expression Of Tfp Genes From Leptospirillum Sp Cf-1 Is mentioning
confidence: 97%
“…In addition to reducing cytoplasmic proteins, thioredoxins are indirectly involved in reducing endogenously-or exogenously-produced inorganic and organic peroxides. In this way, they provide reducing equivalents to thiol-based peroxiredoxins that are responsible for peroxide scavenging activity [6,7].…”
Section: Introductionmentioning
confidence: 99%